Design e inovação em contexto de ensino-aprendizagem - Portugal, Cristina; Moura, Monica [UNESP] (My University, 2014)
This paper presents part of the results of a post-doctoral research project which is called "Hypermedia Design involved with the User Experience". The discussion will be undertaken in this article assumes that the use of a hypermedia environment facing the field of Design can facilitate the process of teaching and learning in an undergraduate degree in Design. The theme that guides the paper of the following question: if the education and training in design does not allow access, involvement and knowledge of the technologies in its primary base that practitioners and researchers are forming for the near future? For both this study focuses on the use of a digital environment by reporting of an experiment of using hypermedia digital book "Design, Education and Technology" as a teaching tool in undergraduate courses in design, results and notes on issues involving interactivity and user experience. The methodology has a qualitative bias, developed along the lines of exploratory research in the form of a case study, lectures, and workshops for the dynamic observation, a questionnaire and analysis of results were applied

Este artigo apresenta parte do resultado de uma pesquisa de pós-doutoramento cujo projeto intitula-se “Design de Hipermídia envolvido com a Experiência do Usuário”. A discussão que será empreendida neste artigo parte do princípio que o uso de um ambiente hipermidiático voltado para o campo do Design pode facilitar o processo de ensino-aprendizagem em um curso de graduação em Design. O tema que norteia o artigo parte da seguinte questão: se o ensino e a formação em design não possibilitam o acesso, o envolvimento e o conhecimento das tecnologias em sua base primordial que profissionais e pesquisadores estamos formando para o futuro próximo? Para tanto este artigo apresenta uma reflexão sobre o uso de um ambiente digital por meio do relato de uma experiência realizada do uso de livro digital hipermídia “Design, Educação e Tecnologia” como recurso pedagógico em cursos de graduação em Design, seus resultados e as observações sobre questões que envolvem a interatividade e a experiência do usuário. A metodologia adotada tem um viés qualitativo, desenvolveu-se nos moldes de uma pesquisa exploratória, sob a forma de um estudo de caso, foram aplicadas palestras, dinâmicas e oficinas para a observação, aplicação de questionário e análise dos resultados encontrados.
Design and innovation in the context of teaching-learning
Keywords: Design; Interaction; User experience; Teaching and learnin; Design; Hipermídia; Mídia digital; Design da informação; Ensino-aprendizagem